1974
DOI: 10.1073/pnas.71.10.3966
|View full text |Cite
|
Sign up to set email alerts
|

A Limited Number of Globin Genes in Human DNA

Abstract: The number of globin genes in human cells was determined by hybridizing DNA from human spleens to 3H-labeled DNA complementary to human globin mRNA. Assuming the rates of reannealing of complementary DNA and cellular DNA are similar, the extent of hybridization of complementary DNA at various ratios of cellular DNA to complementary DNA indicate that there are fewer than 10 globin gene copies per haploid human genome. An alternative analysis of the data, which introduces no assumptions concerning the relative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The RNA was trainslated in a wheat germ cell-free system, and its product was analyzed by cellulose acetate electrophoresis as described (18,19). Cellular DNA was extracted from Epstein-Barr-virus-transformed lymphocytic cell lines from normal subjects and from one of the homozygous Lepore patients (L.P.) as previously described (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA was trainslated in a wheat germ cell-free system, and its product was analyzed by cellulose acetate electrophoresis as described (18,19). Cellular DNA was extracted from Epstein-Barr-virus-transformed lymphocytic cell lines from normal subjects and from one of the homozygous Lepore patients (L.P.) as previously described (20).…”
Section: Methodsmentioning
confidence: 99%
“…The melting temperature of the mRNA:cDNA hybrids was obtained as previously described (25) with micrococcal nuclease to assay thermal stability of the hybrids. The hybridization of globin cDNA to cellular DNA was performed as previously described (20).…”
Section: Methodsmentioning
confidence: 99%
“…Comparable numbers of a-and /8-globin genes have been previously reported in /+-thalassemia DNA as in nonthalassemia DNA (3,4). In the studies reported here, both ,+-and g'-thalassemia DNA were used and shown to contain y-globin genes in amounts comparable to normal DNA.…”
Section: Discussionmentioning
confidence: 97%
“…Preparation of human DNA. DNA was prepared from human spleen and liver of patients with and without (8-thalassemia, as described previously (3,4). DNA from peripheral blood was prepared similarly, except that the blood sample containing white blood cells was washed three times with 10 vol of isotonic saline, frozen, and thawed before washing with 5% sucrose containing 1 mM MgCl2, 1 mM sodium phosphate (pH 6.5), 0.4% deoxycholate, and 0.8% Nonidet P40 (Shell International Ltd., London, England).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation